Tax simplification - An African Perspective - Riël Franzsen (Pretoria University Law Press (PULP), 2019)
Why are tax systems so complex and what are the causes and consequences of such complexity? The simplification of tax systems is one of the most important issues faced today in worldwide efforts to modernise and strengthen government finance and revenue raising capacities. Nowhere is it more important than throughout the rapidly emerging economies of the dynamic African region. This volume brings together contributions in this field from a conference held in South Africa in October 2018 and provides a unique synthesis of knowledge and understanding gained from the specialist expertise and diverse backgrounds brought to the tax simplification debate by those authors.